FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Kirana, Diva Radya; Utami, Dea Ananda; Anugrah, Muhammad Nurfajri; Arianti, Erika Dyah; Pujihastuti, Isti (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2024)
This study was conducted to examine the impact of Capital structure with DAR and DER proxies, Company Size with Revenue and Total Assets proxies, and Dividend policy with Dividend Yield and Dividend per share proxies, on Firm value as the dependent variable with EPS and PBV proxies. This research is quantitative research. Mining sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period is the population that used in this study , which uses purposive sampling as a method in determining the sample. The data used in this study are secondary data downloaded via website of each company. The statistical method of hypothesis testing is Partial Least Square. The results of multiple linear analysis prove that there is a negative and significant influence between the capital structure variable and firm value, there is a positive but insignificant influence between the firm size variable and firm value, there is a positive but insignificant influence between the dividend policy variable and firm value